Pemanfaatan Buah Leunca (Solanum nigrum L.) Dalam Pembuatan Minuman Sari Buah (Utilization of Black Nightshade (Solanum nigrum L.) in the Making of Fruit Juice) - Halim, Yuniwaty; Effendi, Diana; Nurwitri, Caecilia C. (Universitas Pelita Harapan, 2018)
Black nightshade (Solanum nigrum L.) fruit contains many antioxidant compounds, however, utilization of black nightshade as food or beverage product has not been much studied. The research was aimed to determine sugar concentration and acid source used in black nightshade juice making to obtain a product that is acceptable for the panelists and to observe the black nightshade juice quality changes during storage. Sugar concentration used were 10%, 12.5%, and 15%. Acids used were from citric acid, belimbing wuluh (Averrhoa bilimbi) and lime (Citrus aurantifolia). It was found that the selected formulation was black nightshade juice added with 15% of sugar concentration and acid added from belimbing wuluh (Averrhoa bilimbi). This formula has acceptance value of 4.41± 1.357 and the IC50 value of 2118.0582 ± 96.3983 mg/L. Storage was done for 6 weeks in refrigerated temperature. During storage, quality of black nightshade juice decreased after 2 weeks, observed from decrease in its antioxidant activity, total phenolic and flavonoid compound.